EDUCATIONAL ACTIVITY OF THE RUSSIAN ORTHODOX CHURCH IN WESTERN SIBERIA IN THE LATE 19TH AND EARLY 20TH CENTURIES - A. A. Valitov (Russian State Vocational Pedagogical University, 2015)
The paper looks at the educational activities of the Russian Orthodox Church in Western Siberia from the late 19th to the mid-20th century. The analysis of archival material reflects the foundation, development and evolution of parish schools in Western Siberia; the activity of the eparchy inspectors and parish school boards being outlined. The main emphasis is on the Tomsk eparchy - the regional leader in successful primary school development in Western Siberia. For many Russian citizens then, the parish schools were the only available educational institutions. In Western Siberia, the ascetic enlightening activity of the clergymen had a great impact on raising the literacy level; the process being complicated by the vast territories, remoteness of the settlements, and lack of local schools. The research demonstrates the parallel evolution of the parish and civil education, however, the former one was always ahead in many aspects. The competition between the two systems stimulated new effective educational methods and teacher training processes, and contributed a lot to the Russian primary education development. The paper might be of interest to the experts in education and church history, and local historians